Manajemen Pembelajaran dalam Meningkatkan Prestasi Belajar Siswa di MIN 1 Purbalingga - Taufiq Himawan (Ar-Rihlah: Jurnal Inovasi Pengembangan Pendidikan Islam, 2021)
The research aims to reveal about the planning, implementation, and evaluation of learning in improving student achievement. This study uses a qualitative method. This research was conducted at MIN 1 Purbalingga, from March to June 2021. The informants in the study were madrasa heads, teachers, and students. Data collection techniques with interviews, observation and documentation. The validity of the data using triangulation. Data analysis uses the Miles & Huberman model, which consists of data collection, data reduction, data presentation and drawing conclusions. The results of this study indicate that: (1) the teachers carry out lesson planning by making a syllabus, annual program, semester program, KKM, time allocation, learning implementation plans, remedial and enrichment programs. (2) The implementation of learning is carried out by the teachers, including preliminary activities (apperception), core activities (including exploration, elaboration and confirmation) and final activities. Teachers use learning media and apply variations of learning methods. (3) Evaluation of learning is carried out by the teacher and by the head of the madrasah. The teacher carries out an assessment system in the form of learning processes and learning outcomes which involve three domains, namely: cognitive, psychomotor, and affective. The madrasa head supervises regularly to help improve teacher performance.